Simultaneous Estimation and Validation of Rampiril, Losartan Potassium and Hydrochlorothiazide by RP-HPLC in Pure and Pharmaceutical Dosage Form - SREEKANTH, N.; SHIVSHANKER, K.; SHANMUGA PANDIAN, P.; ROOSEWELT, C.; SRINIVASA RAO, G.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A simple, accurate, fast and sensitive RP-HPLC method was developed for the estimation of ramipril (RAM), losartan potassium (LTP) and hydrochlorothiazide (HCTZ) in pure and pharmaceutical dosage form. The quantification was carried out using a C18 column 250 × 4.6 mm id, 5 μm particle size in isocratic mode, with mobile phase comprising of buffer and acetonitrile in the ratio of 60:40 (v/v) pH 2. The flow rate was 1 mL/min and the detection was carried out with UV detector at 210 nm. The retention times were 4.78 1.69 and 3.09 min for RAM, LTP and HCTZ, respectively. The method produced linear response in the concentration range of 10-50, 100-300 and 25-125 μg/mL for RAM, LTP and HCTZ, respectively. The percentage recovery was found to be 99.6, 99.8 and 98.9 for RAM, LTP and HCTZ, respectively. Clavunate potassium used as internal standard in the present study. The method was statistically validated for its linearity, accuracy and precision. The intraday and inter day variation was found to be showing less coefficient of variation having high precision of method.